Training on Survey Techniques and Data Processing for Mapping Areas for Young Surveyors - Fitridawati Soehardi; Winayati winayati; Lusi Dwi Putri (Universitas Lancang Kuning, 2023)
Surveys and Mapping are skills in recording and collecting data and information regarding resources (both natural, social and cultural) based on an adequate area with remote sensing technology. The low interest of young surveyors in exploring surveys and mapping. This is because the surveyors consider that developing expertise in using testing equipment and processing survey and mapping data is quite difficult and expensive. HIMATESI is a student association whose members are young researchers, young surveyors or final year students. Partners realize the need for increased understanding of survey techniques. Universities answer partner problems by providing knowledge about survey technique training and data processing for area mapping as well as tricks for dealing with problems in area measurement free of charge. Community service activities in the form of training on survey techniques and data processing for area mapping are held to provide information about the introduction and use of survey tools such as waterpass, theodolite and Autocad and goggle map applications. The method used in the implementation of this training is lighting, discussion and practice. The results of this training were able to increase participants' knowledge of the use of survey technique tools and data processing for area mapping as well as tricks in overcoming problems in the field regarding area measurement and mapping so that it is hoped that participants will be able to implement the knowledge gained in field implementation later.